Alphaherpesvirus origin-binding protein homolog encoded by human herpesvirus 6B, a betaherpesvirus, binds to nucleotide sequences that are similar to ori regions of alphaherpesviruses. - Inoue, N (1994)
We previously identified a human herpesvirus 6B (HHV-6B) homolog of the alphaherpesvirus origin-binding protein (OBP), exemplified by the herpes simplex virus type 1 UL9 gene product. This finding is of particular interest because HHV-6B is otherwise more closely related to members of the betaherpesvirus subfamily. The prototypic betaherpesvirus, human cytomegalovirus, does not encode an obvious OBP homolog and contains a more complex origin of replication than do alphaherpesviruses. Thus, analysis of the function of the HHV-6B OBP homolog is essential for understanding the mechanism of HHV-6B DNA replication initiation. The HHV-6B OBP homolog, OBPH6B, was expressed in vitro by coupled transcription and translation and in insect cells by infection with recombinant baculoviruses. The expressed protein bound to two DNA sequences located upstream of the HHV-6B major DNA-binding protein gene homolog, within a region that was predicted to serve as an origin of replication on the basis of its sequence properties. The binding sites lie within 23-bp segments and are similar to OBP-binding sites of herpes simplex virus type 1. The two OBPH6B-binding sequences are separated by an AT-rich region and have an imperfect dyad symmetry as do the alphaherpesvirus origin regions. We identified OBPH6B transcripts by reverse transcription PCR in HHV-6B-infected Molt-3 cells. These results suggest that OBPH6B functions in a manner analogous to the alphaherpesvirus OBP and that initiation of HHV-6B DNA replication may resemble that of alphaherpesviruses.